Södras viltfoderhantering vid röjning - Karlström, John (2016)
During the time when the forest is in the plant- and clearing phase, it creates a large amount of food but how does it look after it has been cleared? Last fall, another report showed that it continues with major damage to young pine forests (Skogsstyrelsen 2015). It has also been discussions about how forest companies are cleaning their young forests which is the first stage on how to influence the composition of trees (Sander 2014). There is research on how cleaning affects the wildlife fodder amount and the amount of damage to the trees. Cleaning of broadleaves and point cleaning decreases the damage on the remaining stem (Härkönen 2008; Härkönen 1998) while it is status quo when it comes to top cleaning (Edenius 2015; Härkönen 2008). Leaf cleaning temporarily decreases the amount of fodder (Härkönon 1998) while the top cleaning retaining amount or even increased (Edenius 2015). Södra is Sweden's largest forest owner association with over 50,000 members. When it comes to the cleaning, they have clear guidelines and every year they are doing follow-up on the contractors. However, these follow-ups give no perception of how well the cleaning entrepreneurs follows Södra's guidelines when it comes to the wildlife perspective. The thesis purpose is to see how well Södra´s cleaning guidelines follow today's research. Based on the literature, it has also tested suggestions to the existing follow-ups and these have also been evaluated. Södra's guidelines follows the research available today on the cleaning and how it affects the wildlife but today's cleaning follow-up does not say how well it follows the cleaning standard when it comes to wildlife management measures. There are several ways to improve the current cleaning follow-up but it will demand more on those that do inventory and it will take longer to perform the inventory.